﻿Small reserve but high diversity: butterfly community across an altitudinal gradient in the Brazilian Atlantic Forest - Andrêsa G. Andrade; Cássio Cardoso Pereira; Vinícius F. Sperandei; Tatiana Cornelissen (Nature Conservation, 2023)
The present study aimed to describe the composition of the butterfly community in relation to the altitudinal gradient in the Reserva Particular do Patrimônio Natural (RPPN) Alto-Montana, Serra da Mantiqueira, Minas Gerais, Brazil, and to provide a list of species for the area. We collected samples in the RPPN Alto-Montana along an altitudinal gradient from 1400 to 2100 m, between the dry and rainy seasons of 2018 and 2019. During this period, the sampling method utilizing Van-Someren Rydon traps totaled 3,936 hours and the effort using sweep nets totaled 246 hours. A total of 1,253 butterflies distributed across 124 species and six families of diurnal butterflies were observed (Hesperiidae, Lycaenidae, Nymphalidae, Papilionidae, Pieridae, and Riodinidae). Nymphalidae was the most representative family, followed by Hesperiidae, Pieridade, Lycaenidae, Papilionidae and Riodinidae. Moreover, we recorded 37 species with only one individual (singletons) and 20 species with only two individuals (doubletons), totalling 57 species, which corresponds to 46% of all sampled richness. The rarefaction curve did not reveal a tendency toward stabilization. However, the indices showed slightly higher values for the 124 species sampled. The analysis performed using the Bootstrap estimator predicted a total of 143.22 species (± 10.87 SE), with a further 19 additional species than observed. Chao 1 predicted 153.42 (± 11.82 SE), and Jackknife 1 predicted 164.00 (± 16.29 SE) species, with 29 and 40 additional species than the observed, respectively. Our study contributes to the knowledge of butterfly biodiversity in Serra da Mantiqueira and reveals a high species richness for the RPPN Alto Montana, especially considering the relatively small area. In addition, our study provides the first inventory of butterflies for the RPPN Alto Montana, thus supporting further studies investigating the butterfly richness in the Serra da Mantiqueira region. Finally, our findings of endemic, rare, and endangered butterfly species highlight the relevance of further conservation strategies to be considered for the Protected Area’s Management Plan.